Fire-resistant member with double-sided tape

JP2025020980AActive Publication Date: 2025-02-13DENKA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023124640
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13
Estimated Expiration
2043-07-31

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、経時的な凝集力低下が少ない耐火部材を供給することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020980000001_ABST
    Figure 2025020980000001_ABST
Patent Text Reader

Abstract

To provide a fire-resistant member that is less prone to deterioration of cohesive strength in laminated adhesive layers over time.SOLUTION: A fire-resistant member with a double-sided tape comprises a matrix polymer component, an inorganic compound, a softener, a fire-resistant layer containing a thermally expandable compound, and a double-sided tape, having adhesive layers on both sides of a support, disposed on one or both surfaces of the fire-resistant layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fire-resistant member with double-sided tape. [Background technology]

[0002] As fire-resistant members having fire resistance and an adhesive layer, Patent Documents 1 and 2 are known which use a liquid additive-resistant adhesive layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2017 / 034002 [Patent Document 2] Patent Publication No. 2017-145682 Summary of the Invention [Problem to be solved by the invention]

[0004] The adhesive layer described in the above patent documents is able to suppress component migration to some extent by using a specific formulation. However, because the adhesive layer is laminated directly onto the fire-resistant material, the migration of low molecular weight substances from the fire-resistant material to the adhesive layer is not sufficiently suppressed, and there is an issue of a decrease in the cohesive strength of the laminated adhesive layer over time. Furthermore, when a base layer is provided, there is a problem that the fireproof material may be deteriorated by the solvent used in applying the base layer or by the heat during drying.

[0005] An object of the present invention is to provide a fire-resistant member in which the cohesive strength of the laminated pressure-sensitive adhesive layer decreases little over time. [Means for solving the problem]

[0006] The present inventors have found that the above object can be achieved by providing a laminate including a layer of a pressure-sensitive adhesive and a layer of a fire-resistant material with a specific structure, and have thus completed the present invention.

[0007] That is, according to the present invention, the following inventions are provided. [1] A fire-resistant layer containing a matrix polymer component, an inorganic compound, a softener, and a thermally expandable compound; A double-sided tape having a pressure-sensitive adhesive layer on both sides of a support provided on one or both sides of the fire-resistant layer; A fire-resistant member with double-sided tape. [2] The fire-resistant member with double-sided tape according to [1], wherein the fire-resistant layer contains, relative to 100 parts by mass of the matrix polymer component, 20 to 600 parts by mass of the inorganic compound, 10 to 200 parts by mass of the softener, and 5 to 400 parts by mass of the thermally expandable compound. [3] The fire-resistant member with double-sided tape according to [1] or [2], wherein the inorganic compound contains aluminum hydrogen phosphite. [4] The fireproof member with double-sided tape according to any one of [1] to [3], wherein the thermally expandable compound contains thermally expandable graphite. [5] The fire-resistant member with double-sided tape according to any one of [1] to [3], wherein the pressure-sensitive adhesive layer is a crosslinked acrylic pressure-sensitive adhesive. [6] The fireproof member with double-sided tape according to any one of [1] to [4], which is a sheet or a molded body. [7] A fire-resistant component with double-sided tape described in any one of [1] to [5], used for fire-resistant coating of building materials or steel frames. Effect of the Invention

[0008] According to the present invention, it is possible to provide a refractory member which exhibits little loss of cohesive strength over time. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing an example of a fire-resistant member having a double-sided tape provided on one side of a fire-resistant layer. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a fire-resistant member having a fire-resistant layer with double-sided tape on both sides thereof. [Diagram 3] FIG. 13 is a diagram illustrating a method for producing a joint for a flexibility test. [Figure 4]FIG. 13 is a diagram illustrating the bending direction and angle θ of the joint for flexibility test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Below, we will explain in detail the embodiment of the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0011] <Fireproof material with double-sided tape> The fireproof member of this embodiment is a fireproof member with double-sided tape having a fireproof layer (fireproof material) and a double-sided tape (double-sided tape layer). As shown in FIG. 1, in a fireproof member 1 with double-sided tape, the double-sided tape 5 may be provided on one side of the fireproof layer 3. The double-sided tape 5 is a double-sided tape having adhesive layers 7 (7a, 7b) on both sides of a support 9 which is a substrate. Also, as shown in FIG. 2, in a fireproof member 10 with double-sided tape, the double-sided tape 15 (15a, 15b) is provided on both sides of the fireproof layer 13. The double-sided tape 15 (15a, 15b) is a double-sided tape having adhesive layers 17 (17aa, 17ab, 17ba, 17bb) on both sides of a support 19 (19a, 19b) which is a substrate. The double-sided tape may be provided on the fireproof layer via another layer, but is preferably provided directly on the fireproof layer (directly attached).

[0012] The fireproof member of this embodiment can be manufactured, for example, by bonding a sheet-shaped fireproof material and a double-sided tape. The fireproof member may be a sheet or a molded body. The fireproof member is not limited to a sheet shape. The fireproof material (fireproof layer) and the double-sided tape can be molded and deformed according to the shape of the structure to which the fireproof member is attached, and fireproof members of various shapes may be obtained.

[0013] <Fireproof layer> The fire-resistant layer contains a matrix polymer component, an inorganic compound, a softener, and a thermally expandable compound.

[0014] <Matrix polymer component> As the matrix polymer component, a wide variety of known resins can be used, including, for example, thermoplastic resins, thermosetting resins, elastomers, and combinations thereof.

[0015] Examples of thermoplastic resins include polyolefin resins such as polypropylene resin, polyethylene resin, poly(1-)butene resin, and polypentene resin, polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, polycarbonate resin, polyphenylene ether resin, (meth)acrylic resin, polyamide resin, polyvinyl chloride resin (PVC), novolac resin, polyurethane resin, polyisobutylene, polyvinyl acetate, and ethylene-vinyl acetate (EVA).

[0016] Examples of the thermosetting resin include synthetic resins such as polyurethane, polyisocyanate, polyisocyanurate, phenol resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, and polyimide.

[0017] Examples of elastomers include rubber and thermoplastic elastomers. Thermoplastic elastomers are elastomers that have the property of softening and exhibiting fluidity when heated, and can be distinguished from rubber, which does not have such a property.

[0018] Examples of rubber include natural rubber, isoprene rubber, butylene rubber, butadiene rubber, 1,2-polybutadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, chlorinated butyl rubber, chlorinated polyethylene rubber, ethylene-propylene rubber, ethylene-propylene-diene rubber (EPDM), ethylene-vinyl acetate rubber, chloroprene rubber (CR), chlorosulfonated polyethylene, acrylic rubber, epichlorohydrin rubber, reclaimed rubber and other crosslinkable rubbers, silicone rubber, fluororubber, urethane rubber, and the like.

[0019] Examples of the thermoplastic elastomer include polyolefin thermoplastic elastomers (TPO), polyurethane thermoplastic elastomers, polyester thermoplastic elastomers, polyamide thermoplastic elastomers, polybutadiene thermoplastic elastomers, and polystyrene thermoplastic elastomers (TPS).

[0020] The polystyrene-based thermoplastic elastomer is preferably a block copolymer consisting of a polymer block mainly made of vinyl aromatic hydrocarbon and a polymer block mainly made of conjugated diene. Examples of vinyl aromatic hydrocarbons include styrene, p-methylstyrene, α-methylstyrene, vinylxylene, monochlorostyrene, dichlorostyrene, monobromostyrene, etc., which may be used alone or in combination of two or more. Examples of conjugated dienes include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc., which may be used alone or in combination of two or more.

[0021] Specific examples of polystyrene-based thermoplastic elastomers include styrene-butadiene-styrene (SBS) copolymers, styrene-isoprene-styrene (SIS) copolymers, styrene-ethylene-butylene-styrene (SEBS) copolymers, styrene-isoprene-hydrogenated styrene-isoprene-styrene (SEPS) copolymers, styrene-ethylene propylene (SEP) copolymers, styrene-ethylene propylene-styrene (SEPS) copolymers, styrene-ethylene-ethylene propylene-styrene (SEEPS) copolymers, and styrene-butadiene copolymers. The styrene content of the styrene-based thermoplastic elastomer is, for example, 15% by mass or more and 70% by mass or less, and preferably 20% by mass or more and 60% by mass or less. This content is, for example, 5, 10, 15, 18, 20, 23, 25, 30, 31, 35, 40, 45, 50, 55, 60, 65, and 70% by mass, and may be within a range between any two of the values ​​exemplified here.

[0022] These matrix polymer components may be used alone or in combination.

[0023] <Thermally expandable compound> The thermally expandable compound is not particularly limited as long as it expands when heated, and examples thereof include microspheres, melamine, azo compounds, nitroso compounds, hydrazine derivatives, bicarbonates, vermiculite, kaolin, mica, thermally expandable graphite, etc. Among these, thermally expandable graphite is preferred because of its low expansion initiation temperature, and the thermally expandable compound preferably contains thermally expandable graphite.

[0024] Thermally expandable graphite is a crystalline compound that maintains the layered structure of graphite and is made by treating powders of natural graphite, pyrolytic graphite, etc. with inorganic acids such as sulfuric acid and nitric acid and strong oxidizing agents such as concentrated nitric acid and permanganate. When exposed to temperatures of about 200°C or higher, it thermally expands, for example, by 100 times or more. These powders of natural graphite, pyrolytic graphite, etc. are available in various varieties, including those that have been deoxidized and further neutralized, and any of these can be used.

[0025] The thermally expandable graphite used in the present invention preferably has an average aspect ratio of at least 20. By having an average aspect ratio of at least 20, the thermally expandable graphite can be sufficiently filled inside a frame constituting an opening frame of a fitting such as a fire-resistant resin sash, and can also be suitably used for covering a steel frame.

[0026] The average aspect ratio is the ratio of the average horizontal diameter to the thickness in the vertical direction. Since the thermally expandable graphite used in the present invention is generally flat, the vertical direction can be considered to be the thickness direction, and the horizontal direction can be considered to be the diameter direction, so the aspect ratio is the value obtained by dividing the maximum horizontal dimension by the thickness in the vertical direction. Then, the aspect ratio is measured for a sufficiently large number of graphite pieces, i.e., 10 or more pieces, and the average value is taken as the average aspect ratio. The average particle size of the thermally expandable graphite can also be calculated as the average value of the maximum horizontal dimension. The maximum horizontal dimension and thickness of the thermally expandable graphite can be measured, for example, by using a field emission scanning electron microscope (FE-SEM).

[0027] The content of the thermally expandable compound is 5 to 400 parts by mass, preferably 35 to 300 parts by mass, and more preferably 65 to 200 parts by mass, relative to 100 parts by mass of the matrix polymer component. When the content of the thermally expandable compound is within this range, it is possible to achieve both the thermal expansion ratio and the shape stability of the fireproof material after thermal expansion.

[0028] <Inorganic compounds> Examples of inorganic compounds include metal oxides such as alumina, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, aluminum hydroxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; and glass. Examples of the inorganic fillers include beads, silica-based baluns, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon baluns, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, pearlite, obsidian, perlite, rosin, diatomaceous earth, dehydrated sludge, boron, sodium tetraborate hydrate (borax), glass fibers, silica, clay minerals, and inorganic phosphorus compounds. These may be used alone or in combination of two or more. From the viewpoint of dispersibility, the average particle size of the inorganic compound is preferably 1 to 100 μm as measured by a laser diffraction method.

[0029] <Inorganic phosphorus compounds> The inorganic phosphorus compound includes at least one of a phosphoric acid compound, a phosphorous acid compound, a hypophosphorous acid compound, a metaphosphoric acid compound, a pyrophosphoric acid compound, and a polyphosphoric acid compound.

[0030] Examples of phosphate compounds include aluminum monophosphate, sodium monophosphate, potassium monophosphate, calcium monophosphate, zinc monophosphate, aluminum diphosphate, sodium diphosphate, potassium diphosphate, calcium diphosphate, zinc diphosphate, aluminum triphosphate, sodium triphosphate, potassium triphosphate, calcium triphosphate, zinc triphosphate, magnesium triphosphate, ammonium monophosphate, ammonium diphosphate, tricalcium phosphate, aluminum phosphate, etc.

[0031] Examples of the phosphite compounds include aluminum phosphite, aluminum hydrogen phosphite, sodium phosphite, potassium phosphite, calcium phosphite, and zinc phosphite.

[0032] Examples of hypophosphite compounds include aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, and zinc hypophosphite.

[0033] Examples of metaphosphate compounds include aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, zinc metaphosphate, and sodium hexametaphosphate.

[0034] An example of the pyrophosphate compound is sodium pyrophosphate.

[0035] Examples of the polyphosphate-based compound include ammonium polyphosphate and melamine-modified ammonium polyphosphate.

[0036] The content of the inorganic compound is 20 to 600 parts by mass, preferably 80 to 470 parts by mass, and more preferably 140 to 340 parts by mass, relative to 100 parts by mass of the matrix polymer component. By keeping the content of the inorganic compound within this range, it is possible to achieve both flame retardancy and flexibility.

[0037] The inorganic compound preferably contains aluminum hydrogen phosphite, which tends to improve shape stability after expansion of the thermally expandable compound contained in the fireproof material.

[0038] <Softener> The softener is not particularly limited, but examples thereof include rapeseed oil, cottonseed oil, palm oil, coconut oil, peanut oil, tall oil, pine tar, process oil (paraffinic oil, naphthenic oil, and aromatic process oil), carboxylate plasticizer (phthalic acid ester, adipate ester, sebacic acid ester, maleic acid ester, fumaric acid ester, trimellitic acid ester, citrate ester, oleic acid ester, ricinoleic acid ester, stearic acid ester, glycolic acid ester, etc.), and phosphate plasticizer (tritolyl phosphate, triisopropylphenyl phosphate, etc.). The softener may be used alone or in combination of two or more kinds.

[0039] The content of the softener is preferably 10 to 200 parts by mass, more preferably 40 to 170 parts by mass, and further preferably 70 to 140 parts by mass, relative to 100 parts by mass of the matrix polymer component. When the content of the softener is within this range, both flexibility and flame retardancy can be achieved.

[0040] In this embodiment, the fire-resistant material of the present invention may contain a vulcanizing agent and a vulcanization accelerator used in a normal rubber compound, as long as the effect is not impaired. The vulcanizing agent and the vulcanization accelerator improve the degree of crosslinking of the vulcanizable rubber and improve the strength of the rubber itself. The strength of the rubber can be evaluated by hardness. However, the fire-resistant material of the present invention may not contain a vulcanizing agent and a vulcanization accelerator. In other words, the fire-resistant material of the present invention may not be vulcanized.

[0041] In this embodiment, antioxidants, processing aids, lubricants, organic fibers, tackifiers, and the like that are typically used in rubber compounds may be used in combination, provided that the effects of the rubber compound are not impaired.

[0042] The fireproof layer (fireproof material) of this embodiment can be obtained by kneading the above-mentioned components using a known kneading device such as a Banbury mixer, a kneader mixer, or a two-roll mill, and then molding the mixture into a sheet using a conventional molding method such as press molding, roll molding, extrusion molding, or calendar molding.

[0043] The thickness of the resulting fire-resistant layer is not particularly limited, but is preferably 0.1 to 20 mm, and particularly preferably 0.5 to 10 mm.

[0044] <Double-sided tape having adhesive layers on both sides of the support> The double-sided tape used in this embodiment is composed of a support and an adhesive, and has an adhesive layer on both sides of the support, which is a base material. As the adhesive, a conventionally known adhesive can be used, for example, a rubber-based adhesive, an acrylic-based adhesive, a silicone-based adhesive, a urethane-based adhesive, or a combination thereof. In one embodiment, the adhesive layer is preferably a crosslinked acrylic adhesive. When the acrylic adhesive is an acrylic adhesive crosslinked with an isocyanate compound or the like, migration of low molecular weight substances from the fireproof material to the adhesive layer is suppressed, and the cohesive strength of the laminated adhesive layer over time can be suppressed.

[0045] <Rubber-based adhesive> Examples of rubber-based adhesives include natural rubber-based adhesives, styrene-based thermoplastic elastomer-based adhesives, and butyl rubber-based adhesives.

[0046] <Acrylic adhesive> Examples of the acrylic adhesive include an acrylic adhesive mainly composed of an acrylic acid ester. Usually, an acrylic copolymer is obtained by mixing a (meth)acrylic acid ester monomer component, a functional group-containing monomer, and a polymerization initiator, and polymerizing the monomer component.

[0047] Examples of (meth)acrylic acid ester monomers include butyl (meth)acrylate, 2-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, tridecyl (meth)acrylate, and ethyl (meth)acrylate. Examples of the acrylates include silyl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, benzyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxymethyl (meth)acrylate, and ethoxy-n-propyl (meth)acrylate.

[0048] Examples of functional group-containing monomers include those having a hydroxyl group, a carboxyl group, an epoxy group, an amide group, an amino group, a methylol group, and the like.

[0049] Examples of functional group-containing monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-hydroxyvinyl ether.

[0050] Examples of functional group-containing monomers having a carboxyl group include (meth)acrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, acrylamido-N-glycolic acid, and cinnamic acid.

[0051] An example of the functional group-containing monomer having an epoxy group is glycidyl (meth)acrylate.

[0052] Examples of functional group-containing monomers having an amide group include (meth)acrylamide.

[0053] Examples of functional group-containing monomers having an amino group include N,N-dimethylaminoethyl (meth)acrylate and Nt-butylaminoethyl (meth)acrylate.

[0054] An example of the functional group-containing monomer having a methylol group is N-methylol (meth)acrylamide.

[0055] Other copolymerizable monomers include, for example, N-acrylamidomethyltrimethylammonium chloride, allyltrimethylammonium chloride, dimethylallyl vinyl ketone, N-vinylpyrrolidone, vinyl propionate, vinyl stearate, vinyl chloride, vinylidene chloride, vinyl acetate, and styrene.

[0056] The polymerization initiator is not particularly limited, and examples thereof include azobisisobutyronitrile, azobisisovaleronitrile, benzoyl peroxide, etc. These may be used alone or in combination.

[0057] The adhesive strength and cohesive strength (holding strength) of the acrylic adhesive can be set to any value by using a crosslinking agent, such as a polyisocyanate compound, a polyepoxy compound, a polyaziridine compound, a chelate compound, etc.

[0058] Examples of polyisocyanate compounds include aromatic isocyanates, alicyclic isocyanates, and aliphatic isocyanates. Specific examples of polyisocyanate compounds that can be used include tolylene diisocyanate, 4,4-diphenylmethane diisocyanate, xylylene diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and adducts thereof.

[0059] As the polyfunctional epoxy compound, for example, ethylene glycol diglycidyl ether, terephthalic acid diglycidyl ester, etc. can be used.

[0060] Examples of the polyvalent aziridine compound that can be used include tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, tris[1-(2-methyl)-aziridinyl]phosphine oxide, and hexa[1-(2-methyl)-aziridinyl]triphosphatriazine.

[0061] As the chelating compound, for example, ethyl acetoacetate aluminum diisopropylate, aluminum tris(ethyl acetoacetate), etc. can be used.

[0062] The amount of the crosslinking agent added is preferably 0.1 to 20 parts by mass relative to 100 parts by mass of the acrylic copolymer. If the amount is less than 0.1 part by mass, the composition is too soft, causing problems with retention when applied to a structure. If the amount is more than 20 parts by mass, the composition is too hard, causing poor wettability (adhesion) to the structure.

[0063] The thickness of the obtained adhesive layer is not particularly limited, but is preferably 5 to 200 μm, particularly 10 to 150 μm, and further preferably 15 to 100 μm. If the thickness is equal to or more than the lower limit, the adhesive properties are stable, and if the thickness is equal to or less than the upper limit, adhesive residue is unlikely to occur.

[0064] The support of the double-sided tape used in the present invention may be, for example, a nonwoven fabric such as rayon or polyester, Japanese paper, a plastic film, or a metal foil.

[0065] Examples of plastic films include materials containing one or more of the following polymers: polyester (polyethylene terephthalate, etc.), polyolefin (polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, etc.), polyphenylene sulfide, polyimide, polyetherimide, aromatic polyether ketone (polyether ketone (PEK), polyether ether ketone (PEEK), etc.), polyamide (nylon, aramid, etc.), polyacetate, polyurethane, polyvinyl acetate, ethylene-vinyl acetate copolymer (EVA), polyvinyl chloride, fluororesin (polytetrafluoroethylene, etc.), cellophane, vinylon, polyvinyl alcohol, acrylic resin, polycarbonate, polystyrene, various rubbers, etc.

[0066] In order to increase the adhesion between the support and the pressure-sensitive adhesive layer, the support may be subjected to a corona treatment or an electron beam treatment. Also, a base layer made of a polyester resin, a polyolefin resin, an acrylic resin, an epoxy resin, an amide resin, a urethane resin, a melamine resin, or the like may be provided.

[0067] By providing the support, migration of low molecular weight substances from the fireproof material layer to the pressure-sensitive adhesive layer can be efficiently prevented.

[0068] <Application> The fireproof member of the present embodiment can be used for various purposes, for example, as a fireproof coating for fittings or steel frames, etc. A sealing material according to one embodiment of the present invention is a sealing material for fittings or a fireproof coating material for steel frames, etc., made of the fireproof member. EXAMPLES

[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0070] Details of the components in the tables (Tables 1 to 5) are as follows: The unit of the content of each component in the tables is "parts by mass."

[0071] <Refractory material layer> [Matrix polymer component] Polyvinyl chloride (PVC): "TH-1000" manufactured by Taiyo PVC Co., Ltd. Ethylene vinyl acetate copolymer (EVA): "Evaflex EV460" manufactured by Dow Mitsui Polychemicals Co., Ltd. Epoxy resin: "jER806" manufactured by Mitsubishi Chemical Corporation Epoxy resin hardener: Mitsubishi Chemical Corporation "FL052" - Thermoplastic polyolefin elastomer (TPO): "Milastomer 4010NS" manufactured by Mitsui Chemicals, Inc. - Thermoplastic polystyrene elastomer (TPS): "Tefabloc" manufactured by Mitsubishi Chemical Corporation -Butyl rubber: JSR Corporation "BUTYL268" EPDM rubber: "EPT3092M" manufactured by Mitsui Chemicals, Inc. Chloroprene rubber (CR): "S-40V" manufactured by Denka Co., Ltd. [Inorganic compounds] Calcium carbonate (Ca carbonate): "TA-004" manufactured by Chichibu Lime Industry Co., Ltd. Aluminum hydrogen phosphite (Al hydrogen phosphite): "NSF" manufactured by Taihei Chemical Industry Co., Ltd. [Softener] Process oil: Idemitsu Kosan Co., Ltd. "AH-16" [Thermal expandable compound] Thermally expandable graphite: "SS-3" manufactured by Air Water Chemical Co., Ltd.

[0072] <Adhesive layer> -Butyl acrylate (BA): "Butyl acrylate" manufactured by Mitsubishi Chemical Corporation 2-Hydroxyethyl acrylate (HA): "2-Hydroxyethyl acrylate" manufactured by Tokyo Chemical Industry Co., Ltd. Acrylic acid (AA): "Acrylic acid" manufactured by Mitsubishi Chemical Corporation Azobisisobutyronitrile: 2,2'-azodiisobutyronitrile manufactured by Tokyo Chemical Industry Co., Ltd. Trimethylolpropane modified xylylene diisocyanate crosslinking agent (NCO): "TD-75" manufactured by Soken Chemical Industries, Ltd. Epoxy crosslinking agent: "Tetrad C" manufactured by Mitsubishi Gas Chemical Co., Ltd. Polyethylene terephthalate film: Toyobo Co., Ltd. "E5200" 0.025 mm thick <Double-sided tape> Tape 1: "No. 5000NS" manufactured by Nitto Denko Corporation (total thickness 160 μm, acrylic adhesive, support is nonwoven fabric 70 μm) Tape 2: "W-503" manufactured by Furutokogyo Co., Ltd. (total thickness 1 mm, butyl rubber adhesive, support is polyethylene film 210 μm)

[0073] <Various evaluations> The fireproof members with double-sided tape of the Examples and Comparative Examples were subjected to various evaluations as shown below. The results are shown in the tables (Tables 1 to 5).

[0074] (1) Production of Fireproof Member Samples of Examples 1 to 42 and Comparative Examples 1 and 2 [Example 1]

[0075] -Fireproofing The components shown in the table were kneaded for 2 minutes at 120°C using a 3-liter kneader mixer to obtain a composition. The obtained composition was further pressed using a hot press machine to obtain a sheet-like EPDM rubber-based fire-resistant material having a thickness of 2 mm.

[0076] -Preparation of double-sided tape To a reactor equipped with a thermometer, a stirrer, and a cooling tube, 95 parts by weight of butyl acrylate, 5 parts by weight of 2-hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate were added, and the atmosphere was replaced with nitrogen. Then, the reactor was heated to initiate reflux. Next, 0.1 parts by weight of azobisisobutyronitrile was added as a polymerization initiator to the reactor, and the mixture was refluxed for 5 hours to obtain a solution of an acrylic copolymer. A trimethylolpropane-modified xylylene diisocyanate-based crosslinking agent (manufactured by Soken Chemical Industries, Ltd., product name "TD-75") was mixed into this acrylic copolymer solution in an amount of 3 parts by weight in terms of solid content, and the mixture was stirred to obtain a solution of the acrylic copolymer containing the crosslinking agent. The solution of the acrylic copolymer containing the crosslinking agent was applied onto a release paper and dried to obtain a 0.05 mm thick adhesive layer (one side thickness). This was then attached to both sides of a 0.025 mm thick polyethylene terephthalate support and cured at 40°C for 3 days to obtain a double-sided tape.

[0077] -Fireproofing materials The prepared double-sided tape was attached to one side of a 2 mm thick EPDM rubber-based fire-resistant material to form a fire-resistant member.

[0078] [Example 2] A fire-resistant member was manufactured in the same manner as in Example 1, except that in the adhesive layer, 95 parts by weight of butyl acrylate and 5 parts by weight of acrylic acid were used instead of 95 parts by weight of butyl acrylate and 5 parts by weight of 2-hydroxyethyl acrylate, and the crosslinking agent was an epoxy-based crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Inc., product name "Tetrad C").

[0079] [Example 3] A fire-resistant member was produced in the same manner as in Example 1, except that "No. 5000NS" manufactured by Nitto Denko Corporation (total thickness 160 μm, acrylic adhesive, support is nonwoven fabric 70 μm) was used as the double-sided tape.

[0080] [Example 4] A fire-resistant member was produced in the same manner as in Example 1, except that "W-503" manufactured by Furukawa Electric Co., Ltd. (total thickness 1 mm, butyl rubber adhesive, support is polyethylene film 210 μm) was used as the double-sided tape.

[0081] [Example 5] A fire-resistant member was produced in the same manner as in Example 1, except that no crosslinking agent was used.

[0082] [Example 6] A fire-resistant member was produced in the same manner as in Example 2, except that no crosslinking agent was used.

[0083] [Example 7] A fire-resistant member was produced in the same manner as in Example 1, except that the amount of the crosslinking agent was 0.05 parts by weight.

[0084] [Example 8] A fire-resistant member was produced in the same manner as in Example 1, except that the amount of the crosslinking agent was 0.1 parts by weight.

[0085] [Example 9] A fire-resistant member was produced in the same manner as in Example 1, except that the amount of the crosslinking agent was 19 parts by weight.

[0086] [Example 10] A fire-resistant member was produced in the same manner as in Example 1, except that the amount of the crosslinking agent was 21 parts by weight.

[0087] [Comparative Example 1] A fireproof material was produced in the same manner as in Example 1, except that no support was used.

[0088] [Comparative Example 2] A fireproof material was produced in the same manner as in Example 2, except that no support was used.

[0089] [Example 11] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was changed to PVC, a thermoplastic resin.

[0090] [Example 12] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was changed to EVA, a thermoplastic resin.

[0091] [Example 13] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was a thermosetting epoxy resin.

[0092] [Example 14] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was a polyolefin-based thermoplastic elastomer (TPO).

[0093] [Example 15] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was a polystyrene-based thermoplastic elastomer (TPS).

[0094] [Example 16] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was a rubber-based butyl rubber.

[0095] [Example 17] A fire-resistant member was produced in the same manner as in Example 1, except that the matrix polymer component of the fire-resistant material layer was a rubber-based chloroprene rubber (CR).

[0096] [Examples 18 to 24] The inorganic compound in the fireproof layer is calcium carbonate, and the amount of calcium carbonate is 20 to 600 parts by mass. A fireproof member was produced in the same manner as in Example 1.

[0097] [Examples 25 to 30] A fireproof member was produced in the same manner as in Example 1, except that aluminum hydrogen phosphite was used as the inorganic compound for the fireproof material layer and the blending amount thereof was set to 20 to 600 parts by mass.

[0098] [Examples 31 to 36] A fireproof member was produced in the same manner as in Example 1, except that process oil was used as the softener for the fireproof material layer and the blending amount thereof was set to 10 to 200 parts by mass.

[0099] [Examples 37 to 42] A fireproof member was produced in the same manner as in Example 1, except that heat-expandable graphite was used as the heat-expandable compound for the fireproof material layer and the blending amount thereof was set to 5 to 400 parts by mass.

[0100] The test methods for evaluating the performance of each sample are described below.

[0101] <Flexibility> Two SUS plates, 1 mm thick, 25 mm wide, and 100 mm long, were prepared and placed side by side with a 3 mm gap in the length direction. A 10 mm wide, 100 mm long fireproof member with double-sided tape was attached to the plate to create a joint (Fig. 3). The joint was folded in the opposite direction to the side to which the test piece was attached, and the angle θ at which a crack appeared in the fireproof layer of the test piece was measured (Fig. 4). The flexibility was evaluated according to the following criteria. Note that the larger the angle at which the crack appeared, the better the flexibility. ◎: No cracks even at an angle of 180 degrees ○: Cracks occur at angles between 150 degrees and less than 180 degrees △: Cracks occur at angles of 120 degrees or more and less than 150 degrees ×: Cracks occur at angles less than 120 degrees

[0102] <Thermal expansion> A test piece of fireproof material (before being attached with double-sided tape) with a thickness of 2 mm, width of 30 mm, and length of 30 mm was heat-treated at 300°C for 0.5 hours, and its expansion ratio was measured. Specifically, the volume expansion ratio was calculated by dividing the volume after heat treatment by the volume before heat treatment, and the thermal expandability was judged according to the following criteria. The volume was calculated by actually measuring the thickness, width, and length. ◎: Volume expansion ratio is 6 times or more ○: Volume expansion ratio is 4 times or more but less than 6 times △: Volume expansion ratio is 2 times or more but less than 4 times ×: Volume expansion ratio is less than 2 times

[0103] <Shape stability> After evaluating the thermal expansion properties, a three-point bending test jig (upper pushing side tip R1mm and width 80mm, lower two-point support side R1mm, width 80mm, support distance 20mm) was used to measure the strength (three-point bending fracture strength) of the thermally expanded test piece when it was broken under the condition of a compression speed of 50mm / min. The shape stability after thermal expansion was then evaluated according to the following criteria. ◎: 3-point bending breaking strength is 2.0N or more ○: Three-point bending breaking strength is 1.5N or more and less than 2.0N △: 3-point bending breaking strength is 1N or more but less than 1.5N ×: 3-point bending breaking strength less than 1N

[0104] <Flame retardancy> The oxygen index of the test piece of the fireproof material (before bonding with double-sided tape) was measured using a combustion tester (ON-1 type, manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K6269, and the flame retardancy was judged according to the following criteria. Note that the higher the oxygen index, the higher the flame retardancy. ◎: Oxygen index is 55 or higher ○: Oxygen index is 50 or more and less than 55 △: Oxygen index is 45 or more and less than 50 ×: Oxygen index less than 45

[0105] <Cohesiveness (holding force)> The holding power was measured in accordance with JIS Z 0237. Specifically, the fireproof members with double-sided tape of the examples and comparative examples were left to stand in an atmosphere at 40° C. for one day, and then attached to a stainless steel test plate with a width of 20 mm and a length of 20 mm, and left in an atmosphere at 21° C. with a load of 1 kg applied, and the displacement distance (mm) from the original position after one hour was measured. ◎: Misalignment is less than 2mm ○: Misalignment is 2mm or more and less than 4mm △: Misalignment is 4mm or more, but less than 6mm ×: Misalignment is 6mm or more

[0106] <Cohesion over time (retention over time)> The holding power was measured in accordance with JIS Z 0237. Specifically, the fireproof members with double-sided tape of the examples and comparative examples were left standing in an atmosphere at 40° C. for 7 days, and then attached to a stainless steel test plate with a width of 20 mm and a length of 20 mm, and left in an atmosphere at 21° C. with a load of 1 kg applied, and the displacement distance (mm) from the original position after 1 hour was measured. ◎: Misalignment is less than 2mm ○: Misalignment is 2mm or more and less than 4mm △: Misalignment is 4mm or more, but less than 6mm ×: Misalignment is 6mm or more

[0107] <Adhesiveness (adhesive strength)> The adhesive strength was measured in accordance with JIS Z 0237. Specifically, the fireproof members with double-sided tape of the Examples and Comparative Examples were left to stand for one day in an atmosphere at 40° C., and then attached to a stainless steel test plate with a width of 20 mm and a length of 150 mm, pressed once back and forth with a 1 kg rubber roll, and then left to stand for 20 minutes in an atmosphere at 21° C. The adhesive strength was measured by peeling in the 180° direction at a speed of 300 mm / min. ◎: Adhesive strength is 6N / 20mm or more ○: Adhesive strength is 4N / 20mm or more, less than 6N / 20mm △: Adhesive strength is 2N / 20mm or more, less than 4N / 20mm ×: Adhesive strength is less than 2N / 20mm

[0108] [Table 1]

[0109] [Table 2]

[0110] [Table 3]

[0111] [Table 4]

[0112] [Table 5] [Explanation of symbols]

[0113] 1, 10: Fireproof material with double-sided tape 3, 13: Fireproof layer 5, 15(15a, 15b): Double-sided tape 7(7a, 7b), 17(17aa, 17ab, 17ba, 17bb): Adhesive layer 9, 19 (19a, 19b): Support

Claims

1. a fire-resistant layer containing a matrix polymer component, an inorganic compound, a softener, and a thermally expandable compound; A double-sided tape having a pressure-sensitive adhesive layer on both sides of a support provided on one or both sides of the fire-resistant layer; A fire-resistant member with double-sided tape.

2. 2. The fireproof layer comprises, relative to 100 parts by mass of the matrix polymer component, 20 to 600 parts by mass of the inorganic compound, 10 to 200 parts by mass of the softener, and 5 to 400 parts by mass of the thermally expandable compound.

3. The fireproof member with double-sided tape according to claim 1 or 2, wherein the inorganic compound contains aluminum hydrogen phosphite.

4. The fireproof member with double-sided tape according to claim 1 or 2, wherein the thermally expandable compound includes thermally expandable graphite.

5. 3. The fireproof member with double-sided tape according to claim 1, wherein the pressure-sensitive adhesive layer is a cross-linked acrylic pressure-sensitive adhesive.

6. 3. The fireproof member with double-sided tape according to claim 1, which is a sheet or a molded article.

7. The fireproof member with double-sided tape according to claim 1 or 2, which is used for fireproof coating of building materials or steel frames.

Citation Information

Patent Citations

  • Waterrdispersible pressureesensitive adhesive composition

    JP1981008476A

  • Optical filter for display and surface structure of display

    JP2005022365A

  • Flame-retardant heat-conductive adhesive sheet

    JP2012229392A

  • Adhesive sheet for an image display device, method for manufacturing image display device, and image display device

    JP2014152225A

  • Fireproof sheet and battery

    JP2020136100A